Neuropharmacological Activities of Toddalia Asiatica Root Extract in Swiss Albino Rats - P. Ramalakshmi; P. Annapoorani (The Bioscan, 2024)
The present study was focused to investigate the neuropharmacological (antidepressant) activities of Toddalia asiatica root extract. Antidepressant activities of methanolic extract of Toddalia asiatica root was evaluated by behavioural tests like Locomotor Activity Test, Forced Swimming Test and Tail Suspension Test in male Swiss albino rats. We also examined the neuropharmacological activities by estimating the levels of stress parameters, such as plasma nitrites, plasma corticosterone and malondialdehyde, catalase, glutathione peroxidase and superoxide dismutase in the rat brain homogenates. Methanolic extract of Toddalia asiatica root showed the significant neuropharmacological activity in Swiss albino rats. In both FST and TST, they significantly reduced the duration of immobility and demonstrated dose-dependent activity (p < 0.001). At 400 mg kg-1, it showed far better activity than imipramine in FST (p < 0.001). Our studies indicate that Toddalia asiatica root extract showed significant neuropharmacological activities which may be related to activation of serotonergic, noradrenergic and dopaminergic pathways.